Design, optimization and integration of Doherty power amplifier for 3g/4g mobile communications - Carneiro, Marcos Lajovic (2013)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2013.